Clinical Significance of Staphylococcus aureus in a Single Positive Blood Culture Bottle. (18th December 2021) - Go, John Raymond; Challener, Douglas; Corsini Campioli, Cristina; Sohail, M Rizwan; Palraj, Raj; Baddour, Larry M; Abu Saleh, Omar
Abstract: Clinical significance of a single positive blood culture bottle (SPBCB) with Staphylococcus aureus is unclear. We aimed to assess the significance of an SPBCB by looking at the associated outcomes. We performed a retrospective, multicenter study of patients with an SPBCB with S aureus using data collected from both electronic health records and the clinical microbiology laboratory. Overall, 534 patients with S aureus bacteremia were identified and 118 (22.1%) had an SPBCB. Among cases with an SPBCB, 106 (89.8%) were classified as clinically significant whereas 12 (10.2%) were considered contaminated or of unclear significance. A majority (92.4%) of patients received antibiotic therapy, but patients with clinically significant bacteremia were treated with longer courses (25.9 vs 5.7 days, P  < .001). Significant differences in both frequency of echocardiography (65.1% vs 84.6%, P  < .001) and infective endocarditis diagnosis (3.8% vs 14.2%, P  = .002) were seen in those with an SPBCB compared to those with multiple positive bottles. A longer hospital length of stay and higher 90-day, 6-month, and 1-year mortality rates were seen in patients with multiple positive blood culture bottles. An SPBCB with S aureus was common among our patients. While this syndrome has a more favorable prognosis as compared to those with multiple positive blood cultures, clinicians should remain concerned as it portends a risk of infective endocarditis and mortality.